Effect of Osmotic Dehydration Parameters on Papain Enzyme Activity of Carica papaya L. - Md. Zaki, Nurul Asyikin; A. Darim, Rosmaria; Md. Salleh, Liza; Muhamad, Ida Idayu (2005)
Due to the increasing demands of fruit drink mixes, papaya fruit tea is proposed for commercialization as a nutritious tea drink by maintaining the quality of the processed fruit. The aim of this project is to study the effect of osmotic dehydration parameters on quality of the preserved papaya based on papain enzyme activity. Slices (1.5 x 1.5 x 0.5 cm) and cubes (1.0 cm3) of papaya were treated in solution of sucrose (45, 55 and 65 ÂºBrix) and lactic acid (0, 0.05 and 0.10 M) under specified temperature (30, 40 and 60 ÂºC). Osmotic dehydration process was carried out for 24 hours. Analysis of enzyme reaction was then carried out. Analysis of variance (ANOVA) using Statistica 5.0 was performed to determine the lack of fit and the significance of the product effect of the independent variables on the quality attributes. Preservation of papaya by osmotic dehydration has been proved to increase quality retention.